2007
DOI: 10.1029/2006jd007564
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of radiative forcing of Asian biomass‐burning aerosols during the period of TRACE‐P

Abstract: [1] The regional radiative impact of biomass-burning aerosols in Asia is estimated using the new and detailed emission data during the experimental period of Transport and Chemical Evolution over the Pacific (TRACE-P) in March 2001. Integration of the USA National Oceanic and Atmospheric Administration (NOAA) Hybrid Single-Particle 10 Lagrangian Integrated Transport model (HYSPLIT) and a solar radiative transfer model (CLIRAD-SW) allow us to simulate the spatial and temporal distributions of black carbon (BC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 70 publications
2
36
0
Order By: Relevance
“…Similarly, the ratio obtained from an emission inventory compiled by U.S. EPA (2005) during open biomass burning was 4.7. Wang et al (2007) also reported an OC/BC ratio of 6.5Á8.0 over Indochina, India and South Asia. Figure 15 shows the average DRF of aerosols at the top of atmosphere (TOA), ground surface (SFC) and in the atmosphere (ATM).…”
Section: Impact Of Biomass-burning Aerosols On Aod and Drfmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, the ratio obtained from an emission inventory compiled by U.S. EPA (2005) during open biomass burning was 4.7. Wang et al (2007) also reported an OC/BC ratio of 6.5Á8.0 over Indochina, India and South Asia. Figure 15 shows the average DRF of aerosols at the top of atmosphere (TOA), ground surface (SFC) and in the atmosphere (ATM).…”
Section: Impact Of Biomass-burning Aerosols On Aod and Drfmentioning
confidence: 92%
“…The primary biomass-burning carbon aerosols (BC and OC) play important roles in the radiation budget. Wang et al (2007) indicated that solar absorption by BC within the atmospheric, which increases the radiative heating rate, leads to a significant reduction in solar radiation reaching the surface. On the other hand, OC enhances the reflected solar radiation at the TOA, leading to a cooling effect due to reduced incoming solar radiation to the atmosphere and ground surface.…”
Section: Impact Of Biomass-burning Aerosols On Aod and Drfmentioning
confidence: 99%
“…Smoke that is transported aloft and over the mountain ranges of Burma and Laos is caught in the free tropospheric westerlies, and transported over northern Vietnam into the Pacific Ocean (Tang et al, 2003a,b;Satake et al, 2004;Verma et al, 2008;Lin et al, 2009;Reid et al, 2009) or from Burma (Myanmar) into the Southeastern Tibetan Plateau (Engling et al, 2011). Plumes are frequently shown in these papers to reach as far as Taiwan, including the free troposphere receptor site on Lulin Mountain (Wang et al, 2007;Wai et al, 2008;Lin et al, 2009), southern Japan (Tang et al, 2003a,b;Satake et al, 2004) and Hawaii ). Aircraft observations near Europe even identified one exceptionally large IC pollution and smoke event that had traversed 2/3 of the globe (Stohl et al, 2007).…”
Section: Long-range Aerosol Transport In Indo-chinamentioning
confidence: 99%
“…However, before aerosol radiative forcing can be calculated, reliable values of radiative fluxes are needed. There are several approaches for estimating the reflected shortwave and the emitted longwave radiative fluxes at the top of atmosphere including radiative transfer (Davison et al, 2004;Remer and Kaufman, 2006;Wang et al, 2007;Rajeev et al, 2008) and observational approaches (Christopher et al, 2006). Radiative transfer techniques use narrow-band measurements such as MODIS to infer broadband fluxes, and require numerous assumptions about wavelength dependent surface and aerosol properties.…”
Section: Radiative Fluxesmentioning
confidence: 99%
See 1 more Smart Citation